GASTROINTESTINAL COMPLICATIONS DURING TREATMENT: NON-STEROIDAL ANTI-INFLAMMATORY DRUGS ARE USED IN TREATMENT - Achilov Shokhrukh. (Western European Studies, 2024)
To date, the world medical literature presents a huge amount of data on the side effects of NSAID therapy, primarily on their toxic effects on the gastrointestinal tract (GIT). It is known that NSAID-induced erosive and ulcerative damage can be localized in almost any part of the digestive tract. However, traditionally the subject of discussion is NSAID-induced damage to the mucous membrane of the gastroduodenal zone . Nevertheless, the toxic effects of NSAIDs on the small intestine (NSAID-induced enteropathy), despite the relatively rare discussion in the literature, is much more common than is commonly believed
Keywords: Analysis of treatment outcomes; Republican cientific; Medical Care